Least-Squares Mixed Finite Element Methods for Nonlinear Parabolic Problems (Journal of Computational Mathematics, 2002)
Two least-squares mixed finite element schemes are formulated to solve the initial-boundary value problem of a nonlinear parabolic partial differential equation and the convergence of these schemes are analyzed.